Rescue of Infectious Salmon Anemia Virus (Isav) from Cloned Cdna - Cortez-San Martin, M; Toro-Ascuy, D (Humana Press Inc., 2017)
The piscine Orthomyxovirus called Infectious Salmon Anemia Virus (ISAV) is one of the most important emerging pathogens affecting the salmon industry worldwide. The first reverse genetics system for ISAV, which allows the generation of recombinant ISA virus (rISAV), is an important tool for the characterization and study of this fish virus. The plasmid-based reverse genetics system for ISAV includes the use of a novel fish promoter, the Atlantic salmon internal transcribed spacer region 1 (ITS-1). The salmon, viral and mammalian genetic elements included in pSS-URG vectors allow the expression of the eight viral RNA segments. In addition to four cytomegalovirus (CMV)-based vectors that express the four proteins of the ISAV ribonucleoprotein complex, the eight pSS-URG vectors allowed the generation of infectious rISAV in salmon cells. © Springer Science+Business Media LLC 2017.